The Boom of Colonial Investment : Dutch Political Power in the History of Capital in Indonesia - Eko Ganis Sukoharsono (The Indonesian Journal of Accounting Research, 2013)
The paper is historical. It seeks to explore an understanding of accounting in the range of social and political contexts. Michel Foucault’s theory of “power and knowledge” relations is used to analyse this historical contexts. It argues that the Foucaultian “power and knowledge” analysis could provide a richer way of looking and understanding an aspect of the development of accounting in social and colonial-political contexts in Indonesia. The paper focuses on the case of Indonesian accounting history under Dutch colonialism. It argues that during the period of radical change of the Dutch social and political administration in Indonesia, accounting policies were developed which supported its effect on the Dutch large capital domination and profit orientation in the Indonesian archipelago. The process of Dutch capital accumulation in Indonesia was not used to the welfare of indigenous Indonesians, instead the capital was accumulated to colonise economic territories and mass production.